Determining the utility of minimum F-wave latency alterations in the electrodiagnosis of ulnar neuropathy at the elbow - Abdulkadir TUNÇ; Vildan GÜZEL; Aysel TEKEŞİN; Yıldızhan ŞENGÜL (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Ulnar neuropathy at the elbow (UNE) is the second most common entrapment neuropathy. There is little information about the application of F-wave studies for evaluation of UNE. Objective: The aim of this study was to evaluate the diagnostic value of minimum F-wave (F-min) latency alterations by comparing this with nerve conduction analyses in UNE-suspected patients. Methods: Ninety-four UNE-suspected patients were admitted to this study. Sensory and motor nerve conduction and F-wave analyses on the median and ulnar nerves were performed on both upper extremities. Results: A total of 188 upper extremities of 94 patients were examined. Their mean age was 41.4±12.9 years, and 69 patients were female (73.4%). The mean ulnar-nerve across-elbow motor conduction velocity (MCV) in the affected arms was significantly slower than the velocity in healthy arms. The mean ulnar-nerve F-min latencies were significantly longer in the affected arms. Fifty-one patients were electrophysiologically diagnosed as presenting UNE (54.2%). Significantly slower mean ulnar-nerve across-elbow MCV, longer mean ulnar-nerve F-min latency and longer distal onset latency were detected in UNE-positive arms. Lastly, patients who were symptomatic but had normal nerve conduction were evaluated separately. Only the mean ulnar F-min latency was significantly longer in this group, compared with the healthy arms. Conclusion: Our study confirmed the utility of F-min latency measurements in the electrodiagnosis of UNE. F-wave latency differences can help in making an early diagnosis to provide better treatment options.